A sunless sea - Perry, Anne (Perry, Anne. William Monk novel, 2012)
As commander of the River Police, Monk is accustomed to violent death, but the mutilated female body found on Limehouse Pier one chilly December morning moves him with horror and pity. The victim's name is Zenia Gadney. Her waterfront neighbors can tell him little, only that the same unknown gentleman had visited her once a month for many years. She must be a prostitute, but, described as quiet and kempt, she doesn't appear to be a fallen woman. What sinister secrets could have made poor Zenia worth killing? And why does the government keep interfering in Monk's investigation? While the public cries out for blood, Monk, his spirited wife, Hester, and their brilliant barrister friend, Oliver Rathbone, search for answers. From dank waterfront alleys to London's fabulously wealthy West End, the three trail an ice-blooded murderer toward the unbelievable, possibly unprovable truth, and ultimately engage their adversaries in an electric courtroom duel. But unless they can work a miracle, a monumental evil will go unpunished and an innocent person will hang. This is a novel of intrigue and suspense in which Monk is driven to make the hardest decision of his life.